2006
DOI: 10.1108/13683040610652186
|View full text |Cite
|
Sign up to set email alerts
|

The effect of manufacturing strategies on financial performance

Abstract: PurposeCompanies must use their resources effectively and productively if they are to compete in an increasingly competitive globalized economy. Effective performance measurement can support this competitiveness. To be able to do this, companies must know the factors that influence their performance and manage these factors in an effective manner. This study seeks to investigate the effect of manufacturing strategies of manufacturing companies on their financial performance and also the effect of firm size on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 28 publications
1
26
0
3
Order By: Relevance
“…Thus, our results fully corroborate the findings of Swamidass and Newell (1987) and Swink, Narasimhan and Kim (2005) and, partially, the findings of Amoako-Gyampah and Acquaah (2008), Kazan, Ozer and Cetin (2006), and Ward and Durray (2000). Industrial rivalry, the control variable, not tested by previous studies, was found to have a negative impact on financial performance.…”
Section: Manufacturing Strategies and Organizational Performancesupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, our results fully corroborate the findings of Swamidass and Newell (1987) and Swink, Narasimhan and Kim (2005) and, partially, the findings of Amoako-Gyampah and Acquaah (2008), Kazan, Ozer and Cetin (2006), and Ward and Durray (2000). Industrial rivalry, the control variable, not tested by previous studies, was found to have a negative impact on financial performance.…”
Section: Manufacturing Strategies and Organizational Performancesupporting
confidence: 91%
“…However, quality in our study only influences non-financial performance. Kazan, Ozer and Cetin (2006) examined the effect of manufacturing strategies on the financial performance of 102 firms in Turkey. In line with the findings of our study, cost/flexibility and quality were found to impact financial performance.…”
Section: Manufacturing Strategies and Organizational Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the circumstances to be determined by this research will be based on strategies on manufacturing and supplier selection. In this study, these strategies indicate key performance objectives for an organization to achieve successful results (Chan, 2005;Kazan et al, 2006) Figure 2.…”
Section: Indicated Informationmentioning
confidence: 95%
“…Entre os estudos que focalizam a ADO em pequenas e médias empresas, citam-se as pesquisas de Murphy, Trailer, Hill (1996) ;Jarvis, Curran, Kitching, et al (2000); Smart;Bourne (2001); Laitinen (2002); Garengo, Biazzo, Bititci (2005) ;Haber, Reichel (2005); Ahmad, Berg, Simons (2006); Gumbus, Lussier (2006); Kazan, Ozer, Cetin (2006); Sharma, Bhagwat (2006); Sousa, Aspinwall, Rodrigues (2006); ; Garengo, Nudurupati, Bititci (2007); Smith, Smith (2007) ;Carpinetti, Galdámez, Gerolamo (2008) ;Varma, Wadhwa, Deshmukh, (2008).…”
Section: Introductionmentioning
confidence: 99%